Integrasi Sains, Sosial dan Agama Sebagai Ruang Lingkup Kajian Studi Islam dalam al-Qur’an - Mokhamad Miptakhul Ulum (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
Islam is the last religion to cover all religions. Islam as a complement to all religions has shown welfare for the universe so that it gets the label Islam rahmatan lil alamin. The study of Islamic studies on rahmatan lil alamin is very broad, but in general the universe consists of three main components as provisions for human life, namely science, social and religion. Science means studying the horizons of the universe starting from living or dead objects. Social means teaching the creatures to interact with each other in order to live together. Religion becomes a tendency to strengthen the relationship between science and social forces, meaning that social interaction between creatures has principles in understanding all science and science to find the ultimate truth, namely God, of course, with the power of religion. These three components are contained in the Qur'an which has a positive impact on all beings in the world, both Islamic and non-Islamic.